Transformation of the Russian banking system under sanctions pressure ("Journal "U". Economy. Management. Finance.", 2026)
The purpose of the study is a comprehensive analysis of structural changes in the banking system of the Russian Federation under the impact of sanctions restrictions of 2022–2025. Objectives: to identify key directions of transformation in the banking sector; to assess adaptation mechanisms of credit institutions; to determine the role of the Bank of Russia in ensuring the stability of the financial system; to analyze prospects for further development. Practical significance lies in the possibility of using the findings for developing bank risk management strategies, improving regulatory approaches, and formulating long-term programs for the development of the financial sector under external restrictions.
Keywords: Russian banking system; sanctions pressure; Bank of Russia; national payment system; transformation; macroprudential policy; financial sovereignty